Role of technology as an enabler for gender empowerment: Evidence from the Khyber Pakhtunkhwa province of Pakistan - Begum, Khadija (International Water Management Institute, 2023)
Women constitute a majority of the workforce in agriculture and play a significant role worldwide in crop production. But their contribution largely remains invisible thus their involvement in agricultural policies/ programs continues to be overlooked. This invisibility of women affects their access to new agriculture/ irrigation technologies as mechanical work is considered men’s domain whereas women do all manual labor in the fields. IWMI introduced micro drip irrigation technology to women instead of following the established practice of introducing it to men. Going against the wind was a risk. Would the women show interest in adopting new technology, and would there be a social backlash because of this intentional targeting of women farmers? However, we decided to take this risk, as it would potentially open up new opportunities for women farmers to access new water and agriculture technologies, if successful. These interventions are not just about enhancing women’s skills in agriculture technologies. This is essentially a step towards intentionally transforming gender norms in situations where such interventions are hard to undertake. Enabling women to realize that they can handle new technologies and increase their income – has allowed men to also acknowledge these issues. Small, but important steps have been taken, for example, in breaking the social norms on women’s restricted mobility, by allowing them to travel safely in groups, to the city for attending training programs. This is how gender-responsive technological interventions can lead to transformative change towards a more inclusive, gender-equal society – in situations and contexts, where acting directly on unequal gender relations is challenging.